Sexual Harassment in Indonesia: Problems and Challenges in Legal Protection (Law Research Review Quarterly, 2021)
child is the greatest gift that God gives to the parents to be cared for and the protection of his rights by the people and the State. Children have basic human rights. Attention to the protection of human rights law in children is still minimal by the people and the State. Indonesia as a State of law must be able to protect the rights of children considering they are the future assets of the State that must be protected the protection of their rights. There have been many cases of sexual crimes in children due to lack of care from parents and no respect for the rights of children by the community. Lack of legal awareness by the community causes the victims of sexual crimes in children to continue. This paper is intended to analyze the sexual harassment cases in Indonesia and its challenges in the legal protection for the victims. This research found that the protection for the victims especially children on the sexual harassment still faced many problems, one of is on the legal culture and unclear protection provided by law.